Risk Factors Associated With Outbreaks of Infectious Salmon Anemia (ISA) With Unknown Source of Infection in Norway - Lyngstad, Trude Marie; Qviller, Lars; Sindre, Hilde; Brun, Edgar; Kristoffersen, Anja B. (Frontiers in Veterinary Science, 2018)
The occurrence of infectious salmon anaemia (ISA) outbreaks in marine farmed Atlantic salmon constitutes a recurring challenge in Norway. Here, we aim to identify risk factors associated with ISA outbreaks with an unknown source of infection (referred to as primary ISA outbreaks). Primary ISA outbreaks are here defined by an earlier published transmission model. We explored a wide range of possible risk factors with logistic regression analysis, trying to explain occurrence of primary ISA with available data from all Norwegian farm sites from 2004 to 2016; explanatory variables included site latitude and a range of production and disease data. The mean annual risk of having a primary outbreak of ISA in Norway was 0.7 % during this study period. We identified that occurrence of infectious pancreatic necrosis (IPN), having a stocking period longer than 2 months, sites located at high latitude and high fish density (biomass per cage volume) in the first six months after transfer to sea site as significant risk factors (p < 0.05). We have identified factors related to management routines, other disease problems and latitude that may help understand the hitherto unidentified drivers behind the emergence of primary ISA outbreaks. Based on our findings, we also provide some management advice that may reduce the incidence of primary ISA outbreaks.